ثقافية التنمر المدرسي قراءة سوسيوتربوية - بلوم, اسمهان; مريم, شباح (University of Eloued جامعة الوادي, 2020)
إستئساد ، استقواء بلطجة ، تنمر هي منطلقات راسمة لفضاء مظلة المعرفة السوسيولوجية في رصد تلك التحديات والإشكالات المبلورة لمظاهر فكر التنمر تأسيسا ، تحديثا ومعاصرة ،كمحاولة لمعرفة دلالة حقل التنمر نشأة و مضمونا ،ضمن منظومة معرفية تتأرجح بين الممارسة السلوكية ،الفعل، الفردية و الجماعية بل من الواقعية حتى الافتراضية , تمثل جذور التنمر المدرسي روافد معرفية ابستمية كقواعد حاكمة و موجهة لجهود الباحثين في حقل المعرفة تلك القواعد التي تؤمن سلامة البناء الفكري بطابعه التجريدي و الواقعي لكي يلج التفكير العلمي بمختلف ضروبه، دوره في التعامل مع باثولوجيا التنمر باعتبارها نتاج معرفة مشوهة غير عقلانية نعبر عنها بانفعالات غير معتدلة مضطربة الغرض منها إلحاق الضرر و الأذى بالطرف الأخر ،ليغدوا كترسيمة دلالية قوامها التورط في الاضطهاد اللفظي الجسدي ،قمع حرية الغير و التدخل في أفكارهم، نشر الإشاعة بل وتدمير ملكية الآخرين, تضمن هذه المنطلقات نسق الواجهة المتعددة لصور التنمر المدرسي و تنميطاته الواصفة لنوافذ معرفية متعددة نبغوا من خالها بناء راهنية حوارية تكاشف عن تمظهرات التنمر المدرسي تجلياته ، معاييره و مآلاته الكلمات المفتاحية: ثقافة التنمر ، سيكولوجية التنمر. Abstract: Intimidating, bullying, aggroing, and threateningare the starting points of the sociological knowledge scope in monitoring challenges andstudying issues regarding to fundamental, modern and contemporary bullying features. This study aims to identify the significance of the field of bullying for its comprehensiveness, with regard to both content and form, within a cognitive system that may shift between behavioural, actual, individual and collective practices, depending on the realistic and the unrealistic circumstances. The school-bullying origins are epistemological cognitive rules that are controlling the researchers’efforts and ideas of contributing to knowledge. These rules, however, assure the integrity of an abstract and realistic intellectual construction in order to engagein all aspects of the scientific thinking. Within this aim, intellectual construction role hence lies in dealing with the pathology of bullying as a product of distorted irrational knowledge expressed by unruly emotional disturbances intended to cause damage and harm to the other. Therefore, school bullying became a semantic label, which can be in the forms of verbal, physical and emotional abuses, freedom suppression, rumour dissemination and privacy destruction.These perspectives uncover the multi-faceted format of school bullying and its descriptive patterns of multiple knowledge sources. This paper has clearly shown that the studied issue can be solved through a current process of constructive dialogue that reveals the school bullying aspects, standards and outcomes.
School-Bullying Culture - Socio-Educational Study-
الملتقى الوطني الأول حول المدرسة الجزائرية الإشكالات والتحديات 18- 19 فيفري 2020. جامعة الوادي
Keywords: ثقافة التنمر ، سيكولوجية التنمر; Bullying Culture, Bullying Psychology, Bullying Reality in Algeria